Toleransi Klon Unggul Jarak Pagar Terhadap Cekaman Kelembapan Tanah - . Lestari; . Djumali (Jurnal Ilmu Pertanian Indonesia, 2017)
Jatropha superior clones which will be released as varieties suitable for dryland should have been tested for their level of tolerance to stress of water. The study aimed to determine the level of tolerance of physic nut superior clones. Greenhouse research was carried out in The Research Institute of Sweeteners and Fiber Crops, Malang, East Java in July-November 2015. The treatments were arranged in the split-plot design with three replications. The main plot consists of four levels of soil moisture (40, 60, 80, and 100% of field capacity) and the subplot consists of five clones (HS-49/NTT, PT-7/Lampung, HS-49 x SP-88, SP -88 x IP-1A, and PT-7 x SP-117) and one control clone (IP-3A). The results showed that PT-7 x SP-117 classified as a moderate clone, IP-3A was a very resistant clone and SP-88 x IP-1A, HS-49 x SP-88, PT-7/ Lampung, and HS-49/NTT were resistant clones to soil moisture stress